Emissions of putative isoprene oxidation products from mango branches under abiotic stress - Jardine, Kolby J.; Meyers, Kimberly T.; Abrell, Leif; Alves, Eliane Gomes; Yáñez-Serrano, Ana Maria; Kesselmeier, Jürgen; Karl, Thomas G.; Guenther, Alex B.; Vickers, Claudia Estelle; Chambers, Jeffrey Quintin (Journal of Experimental Botany, 2013)
Although several per cent of net carbon assimilation can be re-released as isoprene emissions to the atmosphere by many tropical plants, much uncertainty remains regarding its biological significance. In a previous study, we detected emissions of isoprene and its oxidation products methyl vinyl ketone (MVK) and methacrolein (MACR) from tropical plants under high temperature/light stress, suggesting that isoprene is oxidized not only in the atmosphere but also within plants. However, a comprehensive analysis of the suite of isoprene oxidation products in plants has not been performed and production relationships with environmental stress have not been described. In this study, putative isoprene oxidation products from mango (Mangifera indica) branches under abiotic stress were first identified. High temperature/light and freeze-thaw treatments verified direct emissions of the isoprene oxidation products MVK and MACR together with the first observations of 3-methyl furan (3-MF) and 2-methyl-3-buten-2-ol (MBO) as putative novel isoprene oxidation products. Mechanical wounding also stimulated emissions of MVK and MACR. Photosynthesis under 13CO2 resulted in rapid (<30min) labelling of up to five carbon atoms of isoprene, with a similar labelling pattern observed in the putative oxidation products. These observations highlight the need to investigate further the mechanisms of isoprene oxidation within plants under stress and its biological and atmospheric significance. © 2013 The Author.
Keywords: 1,3 Butadiene Derivative; Carbon Dioxide; Hemiterpene; Isoprene; Methacrolein; Methylvinyl Ketone; Pentane; Reactive Oxygen Metabolite; Volatile Organic Compound; 2-methyl-3-buten-2-ol; 3-methyl Furan; Annona; Mangifera; Mass Fragmentography; Mass Spectrometry; Metabolism; Oxidation Reduction Reaction; Photosynthesis; Stress, Physiological; Plant Stem; Volatile Organic Compounds; 2-methyl-3-buten-2-ol; 3-methyl Furan; Methacrolein; Methylvinyl Ketone; Reactive Oxygen Species; Volatile Organic Compounds; Annona; Butadienes; Carbon Dioxide; Gas Chromatography-mass Spectrometry; Hemiterpenes; Mangifera; Mass Spectrometry; Oxidation-reduction; Pentanes; Photosynthesis; Plant Stems; Stress, Physiological; Volatile Organic Compounds